Occupational health law - Kloss, Diana M.; Hanning, Nick (John Wiley & Sons, 2020)
"The established reference for all occupational health professionals, Occupational Health Law has been a standard in the field since its first edition published in 1989. Comprehensive but highly readable, and using case law examples throughout to clearly demonstrate the application of topics to practice, it is an essential resource for occupational health nurses and physicians, as well as human resources personnel. This fully updated sixth edition includes new material on European and international law, including content on the International Labour Organisation. It now includes start-of-chapter summaries and is accompanied by digital learning material including short-answer questions and case scenarios. With relevant, informative coverage of the provision of occupational health services, the legal liability of the occupational health professional, and vital content on confidentiality, screening, compensation, and equal opportunity legislation, this is the go-to reference for all health professionals involved with or interested in occupational health. Occupational medicine specialises in the diagnosis, management and prevention of disease due to, or exacerbated by, workplace factors. Occupational physicians and health professionals assess work-related health issues and help people remain in work or return following accident or illness. This combines clinical practice with shaping behaviour of both individuals and organisations. Awareness of relevant law and responsibilities of the workplace, the professional and the health worker is vital to all aspects of practice"--